Handbook of burns volume 2: reconstruction and rehabilitation - Kamolz, Lars-Peter (SpringerWienNewYork)
This volume compiles the perspectives of a multi-author team examining the entire spectrum of burn reconstruction and long-term treatment. Individual chapters cover basic aspects of wound healing and scarring, and those of plastic surgery relating to tissue rearrangement and the use of flaps, as well as the long-term use of skin and skin substitutes. Furthermore, topics such as rehabilitation and scar management are addressed in detail. This part provides detailed reconstruction guidelines divided by anatomic region (e.g. face, hands,…), as well as aspects of future trends and prospects in burn reconstruction, among which are e.g. allotransplantation and bionics. List of contributers - Acute stress disorder and post traumatic stress disorder in individuals suffering from burn injury - Long term consequences of burn injuries - Skin architecture and function - Burn wound healing: pathophysiology - Burn scar treatment - Scar assessment - The future of wound documentation: three-dimensional, evidence-based, intuitive and thorough - Evaluation of mimic function in patients with facial burns by use of the three-dimensional video-analysis - Rehabilitation and scar management - Exercise - Principles of burn reconstruction - Tissue expanders in burn surgery - Burn reconstruction: skin substitutes and tissue engineering - Twelve year follow-up: a clinical study on dermal regeneration - Generation of adipose tissue based in tissue engineering: an overview - Burn reconstuction: neck region - Burn reconstruction: eye region - Reconstruction of the post burn ear - Reconstruction of the perioral region after facial burns - Nasal reconstruction - Reconstruction/correction of burn alopecia - Burn reconstruction: breast - Reconstruction of burn deformities of the lower extremity - Thermal injuries to the foot - Burn reconstruction: hand and upper extremity - Facial transplantation - Modern myoprostheses in electric burn injuries of the upper extremity - Subject index.